A diverse fossil terrestrial arthropod fauna from New Zealand: evidence from the early Miocene Foulden Maar fossil lagerstätte. (29th October 2014) - Kaulfuss, Uwe; Lee, Daphne E.; Barratt, Barbara I.P.; Leschen, Richard A.B.; Larivière, Marie‐Claude; Dlussky, Gennady M.; Henderson, Ian M.; Harris, Anthony C.
<x xml:space="preserve">Abstract</x> Fossil evidence for the evolutionary history of terrestrial arthropods in New Zealand is extremely limited; only six pre‐Quaternary insects (Triassic to Eocene) have been recorded previously, none of Miocene age. The Foulden Maar fossil lagerstätte in Otago has now yielded a diverse arthropod assemblage, including members of the Araneae, Plecoptera, Isoptera, Hemiptera, Coleoptera, Hymenoptera, Trichoptera and Diptera. The fauna significantly emends the fossil record for the Southern Hemisphere, provides an unparalleled insight into a 23‐million‐year‐old New Zealand lake/forest palaeoecosystem and allows a first evaluation of arthropod diversity at a time coeval with or shortly after the maximum marine transgression of Zealandia in the late Oligocene. The well‐preserved arthropods chiefly represent ground‐dwelling taxa of forest floor and leaf litter habitats, mostly from sub‐families and genera that are still present in the modern fauna. They provide precisely dated fossil evidence for the antiquity of some of New Zealand's terrestrial arthropods and the first potential time calibrations for phylogenetic studies. The high arthropod diversity at Foulden Maar, together with a subtropical rainforest flora and fossil evidence for complex arthropod–plant interactions, suggests that terrestrial arthropods persisted during the Oligocene marine transgression of Zealandia.